A klisé ismeretlensége, avagy a kalkulálható világtalanság: Dialógusban Bónus Tibor Édes Annáról írt monográfiájával - Hoványi , Márton (Studia Litteraria, 2018)
In my essay i begin a critical dialogue with the monograph of Tibor Bónus entitled A másik titok (The other Secret). acknowledging its interpretive advantages and force, i question the study (mis)reading the novel Édes Anna regarding the sacred elements that appear in various forms within the novel. along these lines, i mention possible interpretations that could have enriched the results of the study, and also reveal the possible causes of the continuous misreading of the interpretive starting point frequently mentioned by the author, in his words, of the theological or Christian cliché.